2012
DOI: 10.1016/j.juro.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Levels of Androgen Receptor Variant AR-V1 or AR-V7 Do Not Predict Recurrence in Patients with Prostate Cancer at Indeterminate Risk for Progression

Abstract: The AR-V1 or V7 transcript level does not predict recurrence in patients with high grade prostate cancer at indeterminate risk for progression. Grade 3 cancer in mixed grade tumors may differ from 100% grade 3 cancer, at least in AR-V1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…Our findings underscore the importance of understanding the subclonal architecture of CRPC cell lines and tumor tissue when assessing AR-V expression and function. Indeed, there have been conflicting reports about the association of AR-V expression levels with clinical disease progression (22)(23)(24)(25)42), and our findings suggest that this could be related to the variable degree to which heterogeneous CRPC tumors are enriched for AR-V-expressing cells.…”
Section: Discussionmentioning
confidence: 68%
“…Our findings underscore the importance of understanding the subclonal architecture of CRPC cell lines and tumor tissue when assessing AR-V expression and function. Indeed, there have been conflicting reports about the association of AR-V expression levels with clinical disease progression (22)(23)(24)(25)42), and our findings suggest that this could be related to the variable degree to which heterogeneous CRPC tumors are enriched for AR-V-expressing cells.…”
Section: Discussionmentioning
confidence: 68%
“…The functional significance of AR-V7 cytoplasmic expression is not clear; particularly in light of the finding that AR-V7 has a functional NLS-like sequence that enhances efficient nuclear localization (Chan et al 2012). In contrast to these studies that found AR variant levels were predictive of clinical outcome, a separate study that analyzed mRNA levels of AR-V1 and AR-V7 in surgical specimens using branched chain technology found that there was no association between AR variant expression and disease recurrence (Zhao, et al 2012). The difference in AR-V7 mRNA association with disease recurrence between this study and the study by Hu et al (Hu et al 2009) could be due to the methods of measuring AR-V7 (branched chain vs. RT-PCR) in prostate specimens.…”
Section: Introductionmentioning
confidence: 91%
“…One particular AR-V, AR-V7, arises from contiguous splicing of AR exons 1, 2, 3, and cryptic exon 3 (CE3) (10, 12). Expression of exon CE3 as the 3’ terminal exon of AR-V7 has been exploited for development of reverse transcription (RT)-PCR, in situ hybridization (ISH), and RNA-sequencing (RNA-seq) assays to detect AR-V7 mRNA expression in tissues (10, 12, 1518), circulating tumor cells (1925), and blood (26–28) of patients with CRPC. In circulating tumor cells, positivity for AR-V7 expression has been associated with resistance to abiraterone and enzalutamide, but not taxane chemotherapy (19, 20).…”
Section: Introductionmentioning
confidence: 99%